Ground cover ranks at Brooks Range treelines, Alaska (2019-2022) ... - Dial, Roman; Wong, Russell; Maher, Colin; Hewitt, Rebecca; Sullivan, Patrick (NSF Arctic Data Center, 2023)
Cover rankings of ground cover during 2019, 2020, 2021 and 2022 as sampled within n = 553 5-meter (m) radius plots (area = 78.5 square meters), each centered on a selected white spruce adult called "Focal Tree." The purpose of this dataset was to examine spatial variation in ground cover (less than 0.2-0.3 m tall) of the most important genera across the Brooks Range and in relation to local microclimates. It also provides a baseline for future ground cover rankings to determine changes in abundance. Taxa were ranked in order of cover from Rank1 with the most cover down to Rank5 with the lowest cover in most cases. ...